Desempenho agronômico de Abobrinha Italiana em função da adubação fosfatada - Souza, Francisco Irael de (Universidade Federal Rural do Semi-Árido, 2017)
Although there are for fertilization recommendations for commercial cultivation in some regions, there is scarce research that relates the effect of phosphate fertilization on the production of zucchini, mainly for the Northeast region. The objective of this work was to evaluate the agronomic performance of Italian zucchini in function of phosphate fertilization. Two experiments were conducted at the Rafael Fernandes Experimental Farm of the Federal Rural Semi Arid University (UFERSA), being the first between the period of august to november of 2015 and the second of july of september of 2016. The experimental design was a randomized complete block (DBC) in factorial 2 x 5, with four replications. The treatments consisted of the combination of two cultivars, Caserta and Alícia and five doses of phosphorus (0, 40, 78, 120 and 150 kg ha-1 de P2O5). The analyzed variables were average fruit mass, number of fruits per plant; number of commercial fruits per plant, total production, commercial and not commercial, dry mass accumulation and phosphate in plant, phosphoro content in the diagnostic leaf and nutritional efficiency index. Data were submitted to analysis of variance and dose effects were assessed by regression analysis.The increase of the phosphorus doses increased the accumulation and the concentration of phosphorus in the plant and, consequently, increasing the productivity of the zucchini fruits, although it has decreased the agronomic efficiency , physiologic, production, phosphorus use by the plant and recovery phosphorus applied. The P2O5 doses associated with yields maximum were estimated at 140 kg ha-1 for Alicia and 120 kg ha-1 P2O5 for Caserta. In general, the cultivar Alícia obtained a greater productivity compared to Caserta, and the zucchini productivity was lower in the season first compared to the second planting season
Agronomic performance of Italian zucchini as a function of phosphate fertilization
Keywords: Cucurbita pepo L; Fósforo; Produtividade; Eficiência nutricional; Cucurbita pepo L; Phosphorus; Productivity; Nutritional efficiency; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO